Rectal screening displays high negative predictive value for bloodstream infection with (ESBL-producing) Gram-negative bacteria in neonates with suspected sepsis in a low-resource setting neonatal care unit. (December 2020) - Lenglet, Annick; Schuurmans, Jorien; Ariti, Cono; Borgundvaag, Emily; Charles, Kessiane; Badjo, Collette; Clezy, Kate; Evens, Estiver; Senat-Delva, Rodnie; Berthet, Marine; Lekkerkerker, Michiel; McRae, Melissa; et al.
Highlights: Bacterial rectal colonisation should not be used to guide empirical treatment for neonatal sepsis. Concordance in bacterial genus/species in simultaneous blood and rectal isolates from suspected sepsis neonates was low. NPV of detecting Gram-negative bacterial isolates in rectal samples compared with those in blood samples was 81.6%. Abstract: Objectives: We analysed the concordance of rectal swab isolates and blood culture for Gram-negative bacteria (GNB) isolates in neonates with a suspicion of neonatal sepsis admitted to a neonatal care unit in Haiti. Methods: We matched pairs of blood and rectal samples taken on the date of suspected sepsis onset in the same neonate. We calculated the proportion of rectal isolates in concordance with the blood isolates by species and genus. We calculated the negative predictive value (NPV) for GNB and extended-spectrum β-lactamase (ESBL)-producing GNB for all rectal and blood isolate pairs in neonates with suspected sepsis. Results: We identified 238 blood and rectal samples pairs, with 238 blood isolate results and 309 rectal isolate results. The overall concordance in genus and species between blood and rectal isolates was 22.3% [95% confidence interval (CI) 17.4–28.0%] and 20.6% (95% CI 16.0–26.2%), respectively. The highest concordance between blood and rectal isolates was observed for samples with no bacterial growth (65%), followed by Klebsiella pneumoniae (18%) and Klebsiella oxytoca (12%). The NPV of detecting GNB bacterial isolates in rectal samples compared with those in blood samples was 81.6% and the NPV for ESBL-positive GNB was 92.6%. Conclusions: The NPV of rectal swab GNB isolates was high in all patient groups and was even higher for ESBL-positive GNB. Clinicians can use the results from rectal swabs when taken simultaneously with blood samples during outbreaks to inform the (de-)escalation of antibiotic therapy in those neonates that have an ongoing sepsis profile.